Pengaruh Digital Payment, Digital Marketing, Modal dan Literasi Keuangan terhadap Peningkatan Pendapatan Usaha Kecil di Kota Banjarmasin - Pipit Angelia Widiarti; Ibnu Sutomo; Muhammad Hafizh (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of digital payment, digital marketing, capital, and financial literacy on increasing small business income in Banjarmasin City. The research approach used was quantitative correlation with a sample of 45 small businesses in the culinary sector determined through purposive sampling techniques. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS software version 26. The results of the study show that partially or simultaneously, the variables of digital payment, digital marketing, capital, and financial literacy have a positive and significant effect on increasing small business income. Among the variables studied, digital marketing proved to be the most dominant factor in driving increased revenue. These findings confirm that the use of digital technology, effective capital management, and improving financial literacy are important aspects in supporting the sustainability and growth of small businesses, especially in the culinary sector. This research provides practical implications for small business actors to further optimize digital marketing strategies, strengthen financial management, and utilize digital payment services as an effort to increase competitiveness and business revenue.